Choice of Extraction Method for Receiving Extraction from Seeds of Payne Hay with the High Content of Biologically Active Substances - S. S. Belokurov; E. V. Flysyuk; I. E. Smekhova (Разработка и регистрация лекарственных средств)
Introduction Introduction. According to the literature, modern technologies, in particular, extraction in an ultrasonic field, make it possible to obtain concentrates of biologically active substances (BAS) with almost complete preservation of the chemical composition inherent in natural raw materials and high yield of extractive substances. At the same time, the ability to regulate the concentration of recoverable active substances during the technological process opens up prospects for the use of natural components as the main pharmaceutical substance.Aim. The purpose of this study was to select the optimal extraction method for obtaining extracts with a high content of BAS from fenugreek seeds. Materials and methods. Extracts were obtained at a temperature of 60±2 °С, by the method of dynamic maceration using an ultrasonic device. Ultrasonic extraction was performed using an ultrasonic installation I100-6/4. In both cases, purified water and ethanol solutions in various concentrations from 40 to 90% were used as extractants. The ratio of raw materials: extractant was as 1:10 (by weight). A portion of vegetable raw materials (10 g) was placed in a glass and poured 100 cm3 of extractant. Next, maceration or sonication was performed. Maceration was performed with magnetic stirring, the rotation speed was 100 rpm. Extraction was carried out at a temperature of 55–60 °C for 5 hours. Ultrasonic effects on solid plant materials were carried out with an intensity in the range from 17 to 22 kHz for 30–60 minutes.Results and discussion. Studies have allowed to determine the amount of extractives in the seeds of fenugreek hay, and choose the most promising method of extraction to obtain extracts with a high content of biologically active substances. A comparison was made between dynamic maceration and ultrasonic extraction. The most promising was the method of ultrasonic extraction at an oscillation frequency of 22 kHz. For 1 hour of extraction, it was possible to achieve depletion of raw materials. It is established that the content of extractable substances directly proportional depends on the duration of treatment and the frequency of ultrasonic waves. The correlation coefficient was 0.78.Conclusion. Ultrasonic extraction when exposed for 60 minutes allows you to get a greater amount of extractives compared with dynamic maceration. To achieve the same level of extractive substances by the method of dynamic maceration, the raw materials must be processed within 5 hours.